2022
DOI: 10.1111/bjh.18302
|View full text |Cite
|
Sign up to set email alerts
|

Chronic myeloid leukaemia patients at diagnosis and resistant to tyrosine kinase inhibitor therapy display exhausted T‐cell phenotype

Abstract: H. (2022). Chronic myeloid leukaemia patients at diagnosis and resistant to tyrosine kinase inhibitor therapy display exhausted T-cell phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…On the level of the total CD4 + and CD8 + population, we only found a few function markers or even no markers were changed in the PB and BM of patients respectively, however, further analysis of the T cell subsets revealed that the markers representing the activation and proliferation (CD38, HLA-DR, and CD69) (31,32) were decreased in the less differentiated T N and T CM subsets in the DN-CML and TKI-F patients, while gradually recovered in the pre-MMR and MMR patients. In addition, the higher expression of PD-1 on peripheral CD8 + T cells detected in all the patients treated with TKI, especially for TKI-F patients, this consistent with recent research that a higher percentage of PD-1 detected on CD4 + , CD8 + and Treg cells in CML patients resistant to TKI (33), however, on the level of T cell subsets, we can see that the percentage of PD-1 high expression T cell subsets mainly decreased in the patients who achieved MMR but not in TKI-F and Pre-MMR patients. Those results indicated that dynamic monitoring of the changes of these immune phenotypes in the level of T cell subsets may help to predict the effects and outcomes after TKI treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the level of the total CD4 + and CD8 + population, we only found a few function markers or even no markers were changed in the PB and BM of patients respectively, however, further analysis of the T cell subsets revealed that the markers representing the activation and proliferation (CD38, HLA-DR, and CD69) (31,32) were decreased in the less differentiated T N and T CM subsets in the DN-CML and TKI-F patients, while gradually recovered in the pre-MMR and MMR patients. In addition, the higher expression of PD-1 on peripheral CD8 + T cells detected in all the patients treated with TKI, especially for TKI-F patients, this consistent with recent research that a higher percentage of PD-1 detected on CD4 + , CD8 + and Treg cells in CML patients resistant to TKI (33), however, on the level of T cell subsets, we can see that the percentage of PD-1 high expression T cell subsets mainly decreased in the patients who achieved MMR but not in TKI-F and Pre-MMR patients. Those results indicated that dynamic monitoring of the changes of these immune phenotypes in the level of T cell subsets may help to predict the effects and outcomes after TKI treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, previous studies have found that CD80 may prefer to combine with PD-L1 and CTLA-4 if CD80 had an advantage in expression ( 42 ). Several studies have found that CTLA4 expression regulatory T cells accumulated in the leukemia environment of DN-CML patients, while CML cells increased the expression of PD-L1 ( 18 , 33 , 43 ). Therefore, though the expression of CD28 + T cells remains at a normal level, the decreased level of CD86 + DCs and the unbalanced ratio of CD80/CD86 may also prevent the activation of T cells in DN-CML patients.…”
Section: Discussionmentioning
confidence: 99%
“…and T-cell immunoglobulin and mucin-domain containing protein-3 (TIM-3), are overexpressed on T-cells of CML patients at diagnosis [7][8][9] . Interestingly, lymphocyteactivation gene-3 (LAG-3) was expressed on fewer T-cells in CML patients compared with healthy individuals 7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, activated CD8 + CTLs in myeloid leukemias are dysfunctional and fail to eliminate LSCs in vivo (23, 24, 58-60). In CML, T cell exhaustion at diagnosis has been associated with an increased expression of immune inhibitory receptors and a reduced capacity to produce Th1-cytokines compared to patients in remission (59)(60)(61)(62)(63). Similar to CML, gene expression profiling of CD8 + CTLs from AML patients at diagnosis indicate that CTLs in intermediate and high risk AML are less functional than in favorable risk AML and exhibit an exhaustion immune signature (24).…”
Section: The Adaptive Immune System In Leukemiamentioning
confidence: 99%
“…In CML, numbers and frequencies of effector Tregs in peripheral blood and BM are also increased in CML patients at diagnosis and in patients refractory to tyrosine kinase inhibitor (TKI) treatment (59)(60)(61). These effector Tregs are characterized by the expression of the immune checkpoints PD-1, TIM-3 and CTLA-4, all markers for an increased suppressive activity (61). Anatomically, Tregs in CML are widely distributed throughout the BM parenchyma in mice and humans.…”
Section: Tregs In CMLmentioning
confidence: 99%